Mapping Women's Safety and Walkability: Insights from Bibliometric Analysis - Suresh, Sruthi; Parashar, Arshi (Calibrating Urban Livability in the Global South, 2024)
Women safety in urban spaces is of paramount importance as it helps to prevent violences, insecurities, gender differences in the public spaces. Ensuring women safety can enhance women inclusiveness in urban areas and helps them to enjoy the city life in its full dimension as men do. In order to enhance women safety through means of making urban life safer and more comfortable for women, first step would be through creating urban spaces where women can walk freely. The aim of this paper is to incorporate a bibliometric analysis of publications retrieved from Scopus database, that discusses women and walkability and analyse the research trends in this field. To achieve this, VOS viewer is used, which made it possible to identify major trends and clusters that visually present the obtained information. The analysis is achieved under three parameters; co-authorship, co-occurrence and co-citation. Based on the analysis, walkability is becoming more and more important in the context of women's safety, and there is a trend towards increased association between walkability and improved women's safety. The analysis of research trends and future direction can be helpful in shaping policies for women’s walkability and also pointing researchers in important directions for research which helps to develop safer and more inclusive walkability for women.